Impact of Human Development on Turnover Intention with Mediating Effect of Organizational Commitment - Mazra Mairaj Ghori, (Dialogue Social Science Review (DSSR), 2025)
The purpose of this study aimed to investigate the nature of coalition between talent management with turnover intentions. The evidence is collected by local private schools of Karachi, Pakistan. Specifically, this study is done with the aim of testing the mediating role of organization commitment between talent management and employee turnover intentions relationship. Approach of this paper is based on quantitative study. For data collection, this research used a convenience sampling method. The data were collected from 166 private schools teachers of Karachi, Pakistan. The deductive approach used in this paper. This paper is based on exploratory research design. Findings - The finding of this study reveals that the proposed hypothesis is accepted and organization commitment has a significantly negative effect on turnover intention. Talent management and organizational commitment shared positively significant with each other. The researcher faced certain level of limitations while conducting this research that somehow affects the study. Limitation that researcher faced included not having adequate population, delay in online form filling and less time period.